Rapid reporting on fine needle aspiration of breast lumps in outpatients. - Zuk, J A (1989)
A retrospective analysis of the performance and value of fine needle aspiration of symptomatic breast masses in a special outpatient "breast clinic" within a district general hospital was carried out. All but a few aspirations were performed by a group of histopathologists, with, immediate cytological reporting. Fine needle aspiration was more sensitive for detecting malignancy than clinical assessment alone, the sensitivity increasing with the experience of the aspirator. The results compared favourably with those in reported series from specialist centres in the United Kingdom. The value of fine needle aspiration extends to the overall management of patients with breast masses but the results must be assessed in conjunction with the clinical context in view of the possibility of false negative or, more rarely, false positive cytological diagnoses.